Circulating MMP-12 as Potential Biomarker in Evaluating Disease Severity and Efficacy of Sublingual Immunotherapy in Allergic Rhinitis - Yandan Zhou; Min Xu; Wei Gong; Xiaoming Kang; Renzhong Guo; Jie Wen; Dinggang Zhou; Manjing Wang; Dazhi Shi; Qiancheng Jing (Mediators of Inflammation)
Background. Allergic rhinitis (AR) is a highly heterogeneous disease, and allergen-specific immunotherapy (AIT) is an effective treatment. This study aims to evaluate the circulating mas-related G protein-coupled receptor-X2 (MRGPRX2) and matrix metalloproteinase-12 (MMP-12) levels in evaluating disease severity and predicting efficacy of SLIT in AR patients. Methods. We enrolled 110 moderate-severe persist AR patients (AR group) and 40 healthy controls (HC group). Circulating levels of MRGPRX2 and MMP-12 were measured, and their associations with disease severity were evaluated. All AR patients were assigned to receive sublingual immunotherapy (SLIT), and the efficacy was evaluated, and serum samples were collected at 1 year and 3 years after treatment. The correlations between serum MRGPRX2 and MMP-12 and clinical efficacy were assessed. Results. The serum concentrations of MRGPRX2 and MMP-12 were significantly higher in the AR group than the HC group, and the elevated MMP-12 levels were correlated with VAS and TNSS, and serum MRGPRX2 levels were correlated with VAS. Finally, 100 and 80 patients completed 1-year and 3-year follow-up and were classified into effective and ineffective groups. Serum MRGPRX2 and MMP-12 levels were lower in the effective group than the ineffective group. Although serum MRGPRX2 and MMP-12 levels did not significantly change after 1 year SLIT, serum MMP-12 levels were decreased 3 years post-SLIT than baseline and 1 year post-SLIT levels. Receiver operating characteristic (ROC) showed that serum MMP-12 was a potential biomarker for predicting the efficacy of SLIT. Conclusion. Serum MRGPRX2 and MMP-12 appeared to be promising biological indicators in reflecting disease severity in AR patients. Moreover, circulating MMP-12 might serve as a reliable predictor for clinical responsiveness of SLIT.